Investigating Curiosity and Reasoning Through Technology-Based Science Activities: The Role of Photo Journals - Kharisma Ika Nur'aini; Izza Aliyatul Muna (STAI Hubbulwathan Duri, 2025)
This study investigates how students' curiosity and scientific reasoning are expressed through the use of photo journals in learning about food additives. It aims to: (1) characterize students’ questions and answers based on scientific inquiry practices; (2) describe variations in the expression of curiosity among Grade VIII students; (3) examine the relationship between individual curiosity and scientific reasoning; (4) assess students’ levels of curiosity and reasoning; and (5) compare outcomes between students who used photo journals and those who did not. A mixed-methods approach was employed with a sample of 23 eighth-grade students. Data were collected through photo journals, interviews, questionnaires, and classroom observations. The photo journal served as a technological tool to encourage inquiry and reflection. Student questions and responses were categorized into six inquiry-based types, with the most frequent being teleological and cause-effect questions. Both curiosity and reasoning levels were predominantly high (82.61%), with the remaining 17.39% falling into the medium category. The photo journal method enhanced students’ abilities to express curiosity and apply reasoning. The integration of visual technology supported deeper conceptual engagement and reflection. Individual variations in curiosity were found to be associated with levels of scientific reasoning. While the small sample size and time constraints limit generalizability, the study offers valuable insights into fostering scientific literacy through media-based learning.